2022
DOI: 10.3389/fendo.2022.882431
|View full text |Cite
|
Sign up to set email alerts
|

DNA damage repair-related gene signature predicts prognosis and indicates immune cell infiltration landscape in skin cutaneous melanoma

Abstract: BackgroundDNA damage repair plays an important role in the onset and progression of cancers and its resistance to treatment therapy. This study aims to assess the prognostic potential of DNA damage repair markers in skin cutaneous melanoma (SKCM).MethodIn this study, we have analyzed the gene expression profiles being downloaded from TCGA, GTEx, and GEO databases. We sequentially used univariate and LASSO Cox regression analyses to screen DNA repair genes associated with prognosis. Then, we have conducted a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
2
1
0
Order By: Relevance
“…Our study found that compared with the high DDR group, the low DDR group had stronger immune cell infiltration, with immunosuppressive cells such as NK cells and M2 macrophages enriched in the high DDR group, leading to poorer prognosis, while the activated T cells and B cells were more abundant in the low DDR group, resulting in a better prognosis. Moreover, in gastric cancer and melanoma, it has also been found that patients with low DDR scores have significantly increased immune infiltration, consistent with our results ( 43 , 44 ). Studies have shown that changes in tumor DDR pathways are significantly correlated with the response to immune checkpoint inhibitors (ICIs) and can also affect patient survival ( 45 48 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study found that compared with the high DDR group, the low DDR group had stronger immune cell infiltration, with immunosuppressive cells such as NK cells and M2 macrophages enriched in the high DDR group, leading to poorer prognosis, while the activated T cells and B cells were more abundant in the low DDR group, resulting in a better prognosis. Moreover, in gastric cancer and melanoma, it has also been found that patients with low DDR scores have significantly increased immune infiltration, consistent with our results ( 43 , 44 ). Studies have shown that changes in tumor DDR pathways are significantly correlated with the response to immune checkpoint inhibitors (ICIs) and can also affect patient survival ( 45 48 ).…”
Section: Discussionsupporting
confidence: 92%
“…significantly increased immune infiltration, consistent with our results (43,44). Studies have shown that changes in tumor DDR pathways are significantly correlated with the response to immune checkpoint inhibitors (ICIs) and can also affect patient survival (45-48).…”
Section: Discussionsupporting
confidence: 91%
“…The development of GC is associated with mutations in oncogenes, cancer suppressor genes, and DDRrelated genes, such as KRAS and BRCA1/2, which promote genomic instability and carcinogenesis. Based on DNA damage repair, multiple biomarkers with strong predictive effectiveness for prognosis and anticancer treatment have been identified (39)(40)(41). Nevertheless, recent research has mostly focused on the proteincoding genes involved in DDR regulation.…”
Section: Discussionmentioning
confidence: 99%